2016
DOI: 10.1093/jjco/hyv205
|View full text |Cite
|
Sign up to set email alerts
|

High dose radiotherapy with image-guided hypo-IMRT for hepatocellular carcinoma with portal vein and/or inferior vena cava tumor thrombi is more feasible and efficacious than conventional 3D-CRT

Abstract: Objective: To compare the efficacies of conventional three-dimensional conformal radiotherapy and image-guided hypofractionated intensity-modulated radiotherapy treatments in advanced hepatocellular carcinoma patients with portal vein and/or inferior vena cava tumor thrombi. Methods: A total of 118 hepatocellular carcinoma patients with portal vein and/or inferior vena cava tumor thrombi who received external beam radiation therapy focused on tumor thrombi and intrahepatic tumors were retrospectively reviewed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 15 publications
(11 reference statements)
3
20
0
Order By: Relevance
“…The use of 3D conformal radiotherapy (CRT), intensity-modulated radiation therapy (IMRT), image-guided radiation therapy, or stereotactic body radiation therapy is recommended. Image-guided IMRT is superior to 3D CRT [107]. The tomotherapy system is the radiation system designed for image-guided IMRT; it is suitable for patients with multiple lesions.…”
Section: Treatmentmentioning
confidence: 99%
“…The use of 3D conformal radiotherapy (CRT), intensity-modulated radiation therapy (IMRT), image-guided radiation therapy, or stereotactic body radiation therapy is recommended. Image-guided IMRT is superior to 3D CRT [107]. The tomotherapy system is the radiation system designed for image-guided IMRT; it is suitable for patients with multiple lesions.…”
Section: Treatmentmentioning
confidence: 99%
“…Although only targeted therapy of sorafenib is indicated for stage IIIa patients with macrovascular invasion according to the BCLC recommendations, TACE is indicated for lesions with invasion at the second and the more peripheral portal branch in Japan, and even for lesions with portal vein tumor thrombus (PVTT) at the main trunk in China as long as collateral circulation is well-developed. While hepatic arterial infusion chemotherapy (HAIC) is commonly recommended for patients with portal invasion at the main portal trunk or at the first branch by the JSH guidelines, radiotherapies including transarterial radio embolization (TARE) and external radiation are more frequently used for this situation in China (54,55). For highly selective patients at stage IIb and IIIa, surgical resection is still indicated under the following situations: multiple lesions restrained in the same segment or the same lobe; lesions with PVTT in the same half liver which can be removed or resected.…”
Section: Staging and Treatment Algorithmmentioning
confidence: 99%
“…The RR for EBRT of PVTT/BDTT and HVTT in the present study was 51.2 and 88.6%, respectively. Hou et al[37] have also reported that patients with IVC thrombus treated with EBRT had a better RR and longer survival rate than those with PV thrombus. The reason for the superior efficacy of EBRT for HVTT compared to that for PVTT/BDTT is unclear.…”
Section: Discussionmentioning
confidence: 99%